(untitled) - Wolfe, George ([ New York ], 2000)
The Thinkwell work, on the other hand, is superb. The lecturer, George Wolfe, is enthusiastic, knowledgeable and entertaining. The table of contents includes evolution, organic and inorganic chemistry, cell biology, respiration, photosynthesis, molecular genetics, biotechnology, cell reproduction, Mendelian genetics and mutation, population genetics and evolution, evolution of life on earth, animal systems and homeostasis, plant systems and homeostasis, and ecology. With such a wide range of topics, the collection would be very helpful for students in earth history, geology, biology, ecology, and anthropology, among others.
Keywords: Biology,Life sciences